LEXICAL UNITS OF THE SEMANTIC FIELD “MURDER” - Ismoilova , Dilorom (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article discusses the structural linguistics and its crucial methods which are implemented in scientific research. The field theory is considered as one of the effective methods to analyze the structural and semantic peculiarities of the language. The structure of the microfield of "murder" in the English language and the semantic features of its constituents are scrutinized in this article. Also, the synonymic, antonymic, hyper-hyponymic and graduonymic relations of the lexical units connected to this field within the field were analyzed based on the views of the field theory. In particular, the article reflects the results of research on the methodical use of lexical units included in the microfield of "murder". The author deeply analyzed the general and specific semantic features of these components.